IMPLEMENTASI PEMBELAJARAN BAHASA ARAB BERBASIS BUDAYA LOKAL UNTUK MENUMBUHKAN MINAT BELAJAR SISWA DI KERINCI - Susi Satriani (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
This study aims to analyze the implementation of local culture-based Arabic language learning in fostering students' interest in learning in Kerinci. This approach uses local culture as a medium to introduce Arabic in a more relevant and interesting way. The method applied is qualitative-descriptive, with data collection through interviews, observation, and documentation. The results show that local culture-based learning can increase students' interest, as they feel closer to the material presented. Local cultural elements, such as Kenduri Sko tradition, dance, and folklore, are used to introduce vocabulary and expressions in Arabic. With the integration of local cultural elements, students can learn Arabic in a more emotional and contextualized way. This study recommends that teachers integrate local cultural elements more often in Arabic language learning to increase students' engagement and motivation.